Mobitz type II second-degree atrioventricular block: a commonly overdiagnosed and misinterpreted arrhythmia - Barold, S. Serge; Herweg, Bengt (Frontiers in Cardiovascular Medicine, 2024)
Mobitz type II second-degree atrioventricular block (AVB) is an electrocardiographic pattern that describes what appears to be an all-or-none conduction without visible changes in the AV conduction time or PR intervals before and after a single non-conducted P wave. An unchanged PR interval after the block is a sine qua non of Mobitz type II block. 2:1 AVB cannot be classified in terms of type I or type II AVB. The diagnosis of Mobitz type II block AVB requires a stable sinus rate, an important criterion because a vagal surge (generally benign) can cause simultaneous sinus slowing and AV nodal block, which can resemble Mobitz type II AVB. Atypical forms of Wenckebach AVB may be misinterpreted as Mobitz type II AVB when a series of PR intervals are constant before the block. Concealed His bundle or ventricular extrasystoles may mimic both Wenckebach and/or type II AVB (pseudo-AVB). Correctly identified Mobitz type II AVB is invariably at the level of the His-Purkinje system and is an indication for a pacemaker.